FLEXIBLE HOUSING SCHEMES ON HOUSING TYPE 36 IN YOGYAKARTA - Hendra Frisky; Diananta Pramitasari (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2021)
Flexible housing has the potential to be applied in housing type 36 in Indonesia, especially with a focus on the modeling of the flexible housing scheme. But beforehand, potential redundancies and trend patterns of occupant needs must be identified. The research stages are spaciousness, spatial complexity using statistics, and perceptual clarity using repeated modeling and evaluation. There are 28 research data samples taken from type 36 housing developed by Perum perumnas Regional V of Yogyakarta branches i.e. Perumnas Minomartani, Perumnas Condong Catur, Perumnas Guwosari, and Perumnas Trimulyo. The results of the research are change of rooms needs for the inhabitant, transformation of tipology from the house layout, the priority setting of rooms for the inhabitants, linkage among rooms that is efficient for the inhabitant, limitations of flexible housing, and flexible housing schemes.